Pengaruh Proses Handoff Pada Jaringan WLAN Terhadap Kualitas Video Streaming - Shelvi Eka Tassia; Yolen Perdana Sari (CV. Multi Kreasi Media, 2022)
−: WLAN allows Mobile stations (MS) to communicate and manage the network using radio propagation as media transmission. Radio signals that are transmitted from the sender to the receiver can go through many paths, such as reflection, diffraction, Line of Sight and Obstructed LOS, where each signal on the path has a different level of signal strength, delay and phase. The base of the WLAN block is called the cell. Cell is the area covered by wireless communication. This coverage area depends on the propagation strength of the radio signal and the type of construction of the obstacle or physical characteristics of the indoor environment. The mobile station can move freely within the cell area. Each cell on a WLAN requires communication and traffic management. Where this is done by the Access Point (AP) which functions to regulate communication at each Mobile station in the coverage area. The problem that occurs in this WLAN communication network is when there is overlap, the condition where more than one Access Point is covered in one area. Each mobile station will automatically determine the best connection to be captured from an Access Point. Mobile stations must be able to move smoothly from one network cell to another without losing connection. This process is known as handoff. This overlapping coverage area is important in setting up WLAN so that each Mobile station can move freely without network disconnection. The research method is to design an Access Point in the form of a laptop, not like an Access Point in general, and implement it on a WLAN network system. The purpose of designing this system is to reduce the time lapse required when handoff occurs so that it does not affect the quality of the video when streaming. Access Point designed in the Ubuntu 11.04 operating system using the WICD application has been successfully implemented. The design of the WLAN network in this final project is capable of handoff, so that the network connection is maintained when the mobile station switches to Access Point. When a handoff occurs, there is a time lapse or what is called handoff latency, namely when the mobile station moves from one Access Point to another, it is 126.0791 ms. The handoff process occurs when the gain level is around -87 dB, which is measured at a distance of 22 meters from the initial Access Point. As well as streaming that is done when the handoff is disconnected, even though the network is still connected. Streaming will run again, if refreshed first